(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Biology is one of the subjects that students consider difficult. This difficulty arises because students must memorize the facts, principles, and theories taught by the teacher, without paying attention to the student’s need to discover, develop, and apply their own ideas. The use of information technology in learning is an effective solution to overcome low student participation and increase their motivation in the learning process. The purpose of this study is to describe the feasibility of audio-visual media circulation system and describe the effectiveness of audio-visual media in the learning process. This study uses a qualitative approach through a descriptive method. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the study are that the use of audio-visual media in cardiovascular/circulatory materials in the learning of the human circulatory system can increase student activity and learning outcomes. This media can also help convey information more completely and concretely, making it easier for students to understand material that tends to be abstract